Dominasi Transmigran Ponorogo di Kelurahan Ponorogo (Kajian Penyebab dan Pengaruhnya) - Ajeng Sekar Ayu, Monica Diah (Universitas Islam Negeri Raden Intan Lampung, 2021)
The transmigration program has been implemented in Indonesia since the year 1905. The success of this program encouraged more people from densely populated areas to do transmigration into potential areas where the population density was still low. The migrants’ purpose was to obtain security, prosperity, and welface in life. This happened on the Ponorogo Migrants who was seeking a new life in the Urban Village Ponorogo, until they became the dominant group set aside a native of the local area. This study aims to analyze the causes and consequences of the dominance of Ponorogo migrants in the Urban Village Ponorogo. This study is a qualitative study by conducting interview, observation, and literature research. The results of the study show that domination obtained by the migrants to give them credit for also leaving the influence of culture in targeted areas of transmigration. Aspects that are affected by the arrival of the migrants include the language, the art, and the social relations of society.Keywords: transmigrant, Ponorogo, Ponorogo Urban Village.